The role of non-state actors in South Africa’s foreign policy making towards BRICS - Nyakujarah, Loveness (My University, 2017)
The study investigated the role of non-state actors in the formulation of South African policy positions relating to the agenda of the Brazil-Russia-India-China-South Africa (BRICS) Alliance. The study noted global trends which indicate that foreign policy decision making was no longer the preserve of the State. Non-state actors were visibly contributing to foreign policy formulation, influencing and shaping of national positions in relation to decisions that involve other countries or institutions beyond the national borders. A range of state and non-state actors from diverse backgrounds who have engaged in BRICS processes were interviewed. The research findings suggest that South Africa’s membership of BRICS is useful for promoting its geo-political and economic interests in an emerging multi-polar world. The study concluded that when holding dialogues, or engaging in processes on BRICS within the country or with BRICS countries, the government has much to benefit from systematic engagements with non-state actors in all their diversity as it enriches policy outcomes. However, currently there is no optimal engagement strategy between the state and most non-state actors. The study presents building blocks that can be used to develop an engagement strategy that elevates the role of non-state actors in foreign policy making towards BRICS. The research used these building blocks to develop a conceptual BRICS non-state actors’ engagement model that can be adapted to any foreign policy space, dubbed the Jambaya-Nyakujarah foreign policy non-state actors engagement model (LJN FP-NSA engagement model). It is proposed that promoting the national interest in BRICS or any other foreign policy platform be explicitly positioned as the main anchor driving all the levels of engagement on any foreign policy issue. The model also propose that stakeholders understand the primary external arenas of engagement that influence national level debates. The study therefore, put forward a model that seeks to strengthen sector-specific and cross-sector collaboration at the non-state actor level, as well as structured engagements between state and non-state actors.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management Public and Development Management (MM PDM), May 2017
Keywords: Non-state actors--South Africa; Non-governmental organizations